Lipidomics Characterization of Biosynthetic and Remodeling Pathways of Cardiolipins in Genetically and Nutritionally Manipulated Yeast Cells - Tyurina, Yulia Y. (ACS Chem Biol, 2016)
Cardioipins (CLs) are unique tetra-acylated phospholipids of mitochondria and define the bioenergetics and regulatory functions of these organelles. An unresolved paradox is the high uniformity of CL molecular species (tetra-linoleoyl-CL) in the heart, liver, and skeletal muscles—in contrast to their high diversification in the brain. Here, we combined liquid chromatography–mass-spectrometry-based phospholipidomics with genetic and nutritional manipulations to explore CLs’ biosynthetic vs postsynthetic remodeling processes in S. cerevisiae yeast cells. By applying the differential phospholipidomics analysis, we evaluated the contribution of Cld1 (CL-specific phospholipase A) and Taz1 (acyl-transferase) as the major regulatory mechanisms of the remodeling process. We further established that nutritional “pressure” by high levels of free fatty acids triggered a massive synthesis of homoacylated molecular species in all classes of phospholipids, resulting in the preponderance of the respective homoacylated CLs. We found that changes in molecular speciation of CLs induced by exogenous C18-fatty acids (C18:1 and C18:2) in wild-type (wt) cells did not occur in any of the remodeling mutant cells, including cld1Δ, taz1Δ, and cld1Δtaz1Δ. Interestingly, molecular speciation of CLs in wt and double mutant cells cld1Δtaz1Δ was markedly different. Given that the bioenergetics functions are preserved in the double mutant, this suggests that the accumulated MLCL—rather than the changed CL speciation—are the likely major contributors to the mitochondrial dysfunction in taz1Δ mutant cells (also characteristic of Barth syndrome). Biochemical studies of Cld1 specificity and computer modeling confirmed the hydrolytic selectivity of the enzyme toward C16-CL substrates and the preservation of C18:1-containing CL species.